Oblicz:
a. - 8 + (-5) - (-7) + (-13) - (10) - 6 =
b. 24 - (-30) + (-62) - (-18) + (-41) - (-70) =
c. - [- (-12) + (-5)] - [- (-17) - (-3)] =
d. - 12,5 - (-4,8) + (-8,7) -[-(6,4)] =
e. -6,5 - (-2 1/4) + (3 1/2) - (-4,2) + [ -(4 3/4)] =
f. 5,4 + (-1 1/5) - (-6,5) + (-3 1/4) - 7,1 =
g. - {- [- (-3,5)] + [ -(-4 1/4)] - [- (-3 1/3)]} =

1

Odpowiedzi

Najlepsza Odpowiedź!
2010-01-07T16:02:43+01:00
A)- 8 + (-5) - (-7) + (-13) - (10) - 6 = -13+7-29= -6-29=-35
b. 24 - (-30) + (-62) - (-18) + (-41) - (-70) = 54-62+18-41+70=39
c. - [- (-12) + (-5)] - [- (-17) - (-3)] = -[12-5] -[20] = 12+5- 20 = -3
d. - 12,5 - (-4,8) + (-8,7) -[-(6,4)] = -12,5+ 4,8 - 8,7 +6,4= -10
e. -6,5 - (-2 1/4) + (3 1/2) - (-4,2) + [ -(4 3/4)] = -6,5+2,25+3,5+4,2-4,75= -1,3
f. 5,4 + (-1 1/5) - (-6,5) + (-3 1/4) - 7,1 = 5,4 -1,2 +6,5-3,25= -5,55
g.- {- [- (-3,5)] + [ -(-4 1/4)] - [- (-3 1/3)]} = -{-[3,5] +[4,25]- [3,1/3]}= 7,75 - 3,1/3= 7,3/4-3,1/3= 3, 5/12